Human Memories Can Be Linked by Temporal Proximity - Yetton, Benjamin D.; Cai, Denise J.; Spoormaker, Victor I.; Silva, Alcino J.; Mednick, Sara C. (Frontiers in Human Neuroscience, 2019)
Real-world memories involve the integration of multiple events across time, yet the mechanisms underlying this integration is unknown. Recent rodent studies show that distinct memories encoded within a few hours, but not several days, share a common neural ensemble, and a common fate whereby later fear conditioning can transfer from one memory to the other. Here, we tested if distinct memories could be linked by temporal proximity in humans. 74 young adults encoded two memories (A and B) close (3hrs) or far apart (7days) in time. One day after encoding the second memory (B), Memory A was updated by pairing it with electric shock (i.e., fear conditioning). We tested whether memory and fear associated with Memory B would be stronger in the 3hr, compared with the 7-day condition. Results were generally consistent with rodent studies, where we found heightened Memory B fear expression when the two memories were encoded close, but not far apart, in time. Furthermore, there was less forgetting of Memory B in the 3hr compared to 7day condition. Our results suggest that temporally proximal memories may be linked, such that updating one experience updates the other.